A case study about using sophisticated masonry models in practice: The Lethes Theater (c. 1650) - Lourenço, Paulo B. (2000)
In the last forty years an enormous growth in the development of numerical tools for structural analysis has been achieved. Historical structures are particularly difficult to analyse due to the lack of data. Nevertheless, significant information can be obtained from numerical analysis. In this paper, an example of the use of numerical analysis to understand the damage and assess the safety of historical structures is presented. This example demonstrates the possibilities of advanced numerical analyses to tackle engineering problems.